Analysis of the Influence of Psychological Empowerment, Relational Psychological Contract, and Pay Satisfaction on Turnover Intention mediated by Work Engagement in Employees - Husna, Hayatul; Mega, Putri (Syntax Corporation, 2024)
The tendency of generation Z, which is the newest group in the workforce, to leave their jobs is significant both globally and in Indonesia. This research aims to reveal the impact of salary satisfaction, psychological empowerment, and relational psychological contract on turnover intention, with work engagement as a mediator. Using a quantitative research design that adopts a cross-sectional approach, data was obtained from 220 generation Z employees. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research results show that there is a direct influence of psychological empowerment on turnover intention, while the relational psychological contract and salary satisfaction do not have a direct influence. Additionally, work engagement was identified as a mediating factor in the relationship between psychological empowerment, relational psychological contract, pay satisfaction, and turnover intention.